Sulfur nanoparticles transform montmorillonite into an inorganic surfactant applicable in thermoplastics processing. (May 2020) - Mérai, László; Rajkumar, T.; Janovák, László; Sápi, András; Szenti, Imre; Nagy, László; Molnár, Tamás; Bíró, István; Sárosi, József; Kukovecz, Ákos; Kónya, Zoltán
Abstract: We report on the modification of montmorillonite (MMT) with sulfur nanoparticles (S NPs) that yields a MMT/S nanocomposite exhibiting surfactant-like amphiphilic behavior at 80:20 MMT:S weight-to-weight ratio. The new material was successfully used as an inorganic surfactant for the dispergation of carbon black (CB) in High-Density Polyethylene (HDPE). Both the novel inorganic surfactants and the HDPE-based nanocomposite products were characterized rigorously by XRD, TGA-DSC, SEM, TEM, zeta potential measurement, static contact angle measurement, tensile strength analysis, particle charge measurement, and X-ray micro-computed tomography. It was found that the presence of 0.5 wt% MMT/S has no adverse effects on HDPE product quality. On the contrary, the MMT/S additive improves the homogeneity of the distribution of CB particles in the HDPE matrix, which is very important because of the UV stabilization properties of CB. The industrial relevance of this finding is that it demonstrates how the right composite of two cheap and readily available inorganic materials can improve the properties of one of the most widely used thermoplastics. Highlights: Montmorillonite/Sulphur (MMT/S) nanoparticle composites were synthesized. MMT/S improved carbon black dispergation into HDPE. MMT/S is a potential inorganic surfactant for polymer composites.